KEDALAMAN DAN KEPARAHAN KEMISKINAN MASYARAKAT NELAYAN: Studi dengan Pendekatan Ekonomi dan Sosial - Mochamad Ridwan; Izharudin Izharudin (Universitas Bengkulu, 2021)
The crucial problem faced by the fishermen community, especially traditional fishermen in rural areas is the problem of poverty depth and severity. The purpose of this study is to identify the index of poverty depth and severity in the fishermen community and to reveal the causes of its occurrence through empirical and theoretical studies with economic and social approaches. This study is survey research by taking the case of fishermen community in the rural coastal of Bengkulu. The selected village as the sample area is Pasar Palik Village, Air Napal Sub-District, Bengkulu Utara District. Data analysis was carried out using the quantitative method and the qualitative-descriptive method. The results show that the poverty depth and severity indexes of the fishermen community are considered quite high (poverty that occurred in the fishermen community is quite deep and quite severe). Other results show that the high depth and severity of poverty in the fishermen community (traditional fishermen) stems from the low ability of fishermen as proxied by low effort (capture fisheries facilities and infrastructure), primordial capital system (patron-client), and the marketing system (marketing channels) is not conducive/not open.